Evaluation of the relationship between window's energy-saving efficiency and the emissivity through simulations - Shi, Yan Wen (Nanyang Technological University, 2021)
Energy crisis becomes a highly focused problem internationally. Window, as the most energy inefficient part in building envelope, has become the bottle neck for building energy efficiency improvement. The conventional approach to improve window energy efficiency is through chromogenic technique to regulate solar transmissions. However, long-wave infrared (LWIR, 2.5 µm – 25 µm) emissivity, which relates to radiative cooling and warm keeping of window is seldom researched. In this report, the effect of front and back side emissivity in relation to window energy efficiency in different climate zones were systematically researched using energy simulation tool, EnergyPlus™. Cities in different zones include Singapore, Cairo, Shanghai, Madrid, Denver, and Moscow. Results showed that compared to the back side emissivity, front side emissivity plays a domination role on window energy saving across all climate zones. Low back side emissivity is preferred globally while the optimised front side emissivity depends on the season and region. Recommended front and back side emissivity values for different regions and seasons were summarised in this report. Suggestions for future study were also provided.